PREDIKSI JUMLAH PENONTON VIDEO YOUTUBE MENGGUNAKAN MODEL DEEP NEURAL NETWORK (DNN) - Dwin Indrawan; Sena Ramadona Cakrawijaya; Bagus Dwi Wicaksono; Erni Erni; Windu Gata (Journal of Information System, Informatics and Computing, 2021)
Youtube viewer becomes a major factor in a content creator's success. The problem is how can predict the number of viewers of a youtube content to determine the success of a content or make it a trending video topic. A machine or computer can predict the number of viewers using the ANN method. DNN is one of ANN models that can predict a dataset. This study compared the success rate in predicting the number of viewers of youtube content from Youtube API dataset. DNN model prediction results have a higher level of excellence compared to the use of traditional methods Linear Regression and Naive Bayes.